Perspective: Identification of genetic variants associated with dopaminergic compensatory mechanisms in early Parkinson's disease - Greenbaum, Lior; Lorberboym, Mordechai; Melamed, Eldad; Rigbi, Amihai; Barhum, Yael; Kohn, Yoav; Khlebtovsky, Alex; Lerer, Bernard; Djaldetti, Ruth (Frontiers in Neuroscience, 2013)
Parkinson's disease (PD) is slowly progressive, and heterogeneity of its severity among individuals may be due to endogenous mechanisms that counterbalance the striatal dopamine loss. In this perspective paper, we introduce a neuroimaging-genetic approach to identify genetic variants, which may contribute to this compensation. First, we briefly review current known potential compensatory mechanisms for premotor and early disease PD, located in the striatum and other brain regions. Then, we claim that a mismatch between mild symptomatic disease, manifested by low motor score on the Unified PD Rating Scale (UPDRS) and extensive Nigro-Striatal degeneration, manifested by reduced uptake of [123I]FP-CIT is indicative of compensatory processes. If genetic variants are associated with the severity of motor symptoms, while the level of striatal terminals degeneration measured by ligand uptake is taken into account and controlled in the analysis, then these variants may be involved in functional compensatory mechanisms for striatal dopamine deficit. To demonstrate feasibility of this approach, we performed a small "proof of concept" study (candidate gene design) in a sample of 28 Jewish PD patients, and preliminary results are presented.